DYNAMICS OF ISLAMIC BOARDING SCHOOLS IN FACING GLOBALIZATION: INTEGRATION BETWEEN TRADITION AND MODERNITY - Ma’isyah, Mukfiyah; Rizal, Mohammad Syifaur; Iqna’a, Faiq Julia; Setiawan, Bakron Andre; Agus R, Abu Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the integration model of tradition and modernity in education at the Miftahul Ulum Besuki Islamic Boarding School, Situbondo. This Islamic boarding school demonstrates the ability to maintain traditional principles in teaching Islam while adopting modern elements relevant to the times' needs, such as technology, foreign languages, and entrepreneurial skills. This study uses a qualitative approach with interview methods and field observations, as well as an analysis of the curriculum and management of the Islamic boarding school. The research findings show that this Islamic boarding school has successfully created a balance between teaching religious knowledge through yellow books and introducing practical skills that are important for students, such as computer skills and entrepreneurship. Although limited by infrastructure, technology enriches the learning process, provides students with access to learn more widely, and prepares them to face the challenges of an increasingly digital global world. In addition, this Islamic boarding school also integrates modern subjects while maintaining the moral and spiritual values that are the basis of Islamic boarding school education. The challenges faced, especially regarding limited technology and resources, can be overcome through cooperation between the Islamic boarding school and external parties who care about education. In conclusion, Miftahul Ulum Besuki Islamic Boarding School is a successful example of combining tradition and modernity, producing students who have a good command of religious knowledge and the practical skills needed to adapt to the development of an increasingly competitive and digital world.